Persepsi inter-aktivitas khalayak terhadap film interaktif â€œBandersnatchâ€ - Fatina, Nadiah Nur; Irwansyah, Irwansyah (Jurnal Studi Komunikasi, 2020)
Interactive stories that were developed in video games and storybooks are now applied to films. With the interaction concept in a film, the audience would not be enjoying linear narrative, but also could help in determining the storyline according to the available choices. The interactive story wants to obscure the passive and active action in audio-visual technology andcreate an intense interaction with humans and the computers to grow stronger emotions between the audience and the movie character or the story. This study used qualitative methods with interview techniques for each person regarding third-order dependency, social presence, and emotions that are built when watching the interactive movie, â€œBandersnatchâ€. The experience of watching while participate in choosing the storyline, build an intense interaction, satisfaction and made humans as audiences feel closer and feel the emotions of the movie character.